NILAI DAN PRINSIP ISTIQĀMAH DALAM PENDIDIKAN QUR’ANI: Kajian Tematik Kisah Nabi Yusuf - Qonitah Hisyam Amar (STAI AL-ANWAR SARANG, 2025)
Qur’ānic education plays a strategic role in shaping Muslims' moral character by instilling the values embedded in the Qur’ān. Nevertheless, studies that systematically extract the concept of istiqāmah from the story of Prophet Yūsuf and relate it to the framework of Qur’ānic education remain limited. This study aims to identify the values and principles of istiqāmah in the story of Prophet Yūsuf and to analyze their implications for Qur’ānic education in the context of contemporary moral challenges. The research employs a qualitative thematic tafsīr method. The primary data consist of the verses of Sūrat Yūsuf, while the secondary data are drawn from classical exegetical works such as those of Ibn Kathīr, al-Qurṭubī, and al-Sa‘dī. The analysis was conducted in three stages: interpreting the verses according to the exegetes, extracting the values and principles of istiqāmah, and formulating their pedagogical implications for Qur’ānic education. The findings reveal that the values of istiqāmah include patience, safeguarding chastity and honor, preaching under pressure, and compassion and tolerance, while its principles include steadfastness in faith, moral integrity, perseverance in facing trials, and the preservation of social relationships. These findings provide a conceptual foundation for the development of Qur’ānic education oriented toward character strengthening and social harmony.